PENINGKATAN HASIL BELAJAR BAHASA INDONESIA TENTANG KEMAMPUAN BERBICARA MELALUI METODE ROLE PLAYING - Muawanah Muawanah (LPPM UNISDA, 2017)
The purpose of this research is to improve learning result and speech ability by using role playing method on grade V SDN Weru II Paciran Lamongan. This research is in the form of Classroom Action Research (PTK). The subjects used in this study are the students of grade V SDN Weru II Paciran Lamongan amounted to 20 students consisting of 11 male students and 9 female students. Data collection techniques used are observation and test. Data analysis technique used is with qualitative and quantitative deductive analysis. The research process is carried out in two cycles. Each cycle consists of four stages: (1) action planning, (2) action implementation, (3) observation, and (4) reflection. Based on the result of research, it can be concluded that Role Playing method can improve learning result and speaking ability in grade V SDN Weru II Paciran Lamongan. This can be proved by increasing the percentage of completeness per cycle. At the pre cycle Student completeness only reached 25% with the average score of 61 students, in the first cycle increased by 29% to 54% with the average student reaches 70, and in the second cycle increased again by 26% to 80% with an average student score of 90.